2019
DOI: 10.1016/j.humpath.2019.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Plasmacytoid/diffuse urothelial carcinoma: a single-institution immunohistochemical and molecular study of 69 patients

Abstract: Accurate diagnosis of plasmacytoid urothelial carcinoma (PUC) is important given its poor prognosis and frequent presentation at high stage. We aim to assess the clinicopathologic features, molecular aberrations, and follow-up data in a series of PUC cases from a single tertiary cancer center. Seventy-two urinary bladder, ureteral, and renal pelvic specimens with urothelial carcinoma with plasmacytoid differentiation were identified. Immunohistochemical (IHC) stains were performed on 48 cases. Among urinary bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 30 publications
3
34
0
Order By: Relevance
“…1), along with the increased frequency of localized and peritoneal recurrence (Table 4) are consistent with this finding. E-cadherin loss in 57% of PUC specimens has also been reported by others, including Perrino et al [19]. These authors described stratification of PUC into desmoplastic, classic and pleomorphic morphology, with loss of E-cadherin being more prominent in the last two categories, while 9p21 deletion and FGFR3 mutations were frequently identified, providing insight on molecular pathogenesis and potential therapeutic targets.…”
Section: Discussionsupporting
confidence: 68%
“…1), along with the increased frequency of localized and peritoneal recurrence (Table 4) are consistent with this finding. E-cadherin loss in 57% of PUC specimens has also been reported by others, including Perrino et al [19]. These authors described stratification of PUC into desmoplastic, classic and pleomorphic morphology, with loss of E-cadherin being more prominent in the last two categories, while 9p21 deletion and FGFR3 mutations were frequently identified, providing insight on molecular pathogenesis and potential therapeutic targets.…”
Section: Discussionsupporting
confidence: 68%
“…A previous study by some of our co-authors demonstrated pathogenic CDH1 mutations in the majority of PUC [26]. Deletions of chromosome 9p21 have been reported to play an important role and TP53 mutations are present in a minority of PUC [22, 27]. FGFR3 mutations have been detected in approximately 60% of cases [27].…”
Section: Introductionmentioning
confidence: 96%
“…Deletions of chromosome 9p21 have been reported to play an important role and TP53 mutations are present in a minority of PUC [22, 27]. FGFR3 mutations have been detected in approximately 60% of cases [27]. In a recent study of 69 cases of PUC, three morphologic subtypes (classic, desmoplastic, and pleomorphic) were identified, and the desmoplastic group was found to have shortest survival (10 months) [27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, immunohistochemically, the expression of ZEB1 reduced E-cadherin expression in the sarcomatous component of other cancers [11]. In contrast, although it has been reported that a plasmacytoid urothelial carcinoma loses E-cadherin expression [12], there have been no reports stating whether or not ZEB1 contributes to the tumorigenesis of a plasmacytoid urothelial carcinoma.…”
Section: Introductionmentioning
confidence: 99%